An analysis of the South African tax treatment of interests in foreign companies held through foreign trusts - Swart, Melishe (North-West University (South Africa), 2021)
South Africa is a high rate tax country and it is common for taxpayers to develop global avoidance strategies to reduce the amount of tax they are liable for. This pertains especially to taxpayers in the international trade sector since South Africa changed to a worldwide income-tax base. (Oguttu, 2007:10). One of the anti-avoidance provisions included in the Income Tax Act (58 of 1962) is the controlled foreign company regime. Where a foreign discretionary trust controls a foreign company, as stated in the definition of a controlled foreign company and a resident is a beneficiary of the foreign trust, that resident is not necessarily subject to tax in accordance with the controlled foreign company rules. Whether or not they will be subject to tax will depend on the indirect participating rights the beneficiary may hold in the foreign company. The controlled foreign company rules do not include foreign trusts and certain foreign foundations, depending on how the structure is viewed by the resident country of the foreign foundation. Residents can thus possibly escape the controlled foreign company rules in the tax legislation by using a foreign trust or a foreign investment vehicle other than a company to directly hold the voting and participating rights in a controlled foreign company. National Treasury has raised concerns that a foreign company held by a foreign trust is not included in the tax net of the controlled foreign company regime. In 2018, National Treasury addressed this concern by expanding the trust anti-avoidance rules to exclude the foreign dividend exemption for residents of South Africa if the dividends received by the resident arose as a result of a controlled foreign company held by the foreign trust (National Treasury: 2018:41). The question arises as to whether the attempt to exclude the foreign dividend exemption is sufficient to protect the tax net of South Africa. Australia has two anti-avoidance measures that can address the taxation of foreign companies held by foreign trusts. Connected foreign trust rules, included as part of the controlled foreign company regime in the Income Tax Assessment Act (1936) and the Transferor Trust anti-avoidance measures, are intended to capture structures that do not adhere to the requirements of the connected foreign trust provisions. The aim of this study was to analyse the connected foreign trust and transferor trust rules included in Australian legislation to include profits from foreign companies held by foreign trusts to determine what mechanism used by Australia, if any, can be considered to reduce the inconsistencies in the ITA of South Africa. Based on the analysis performed on both South African and Australian legislation, it is determined that the control tracing interest principle included in the connected foreign trust rules in Australia should be considered by South Africa to address the inconsistency in the ITA as a primary mechanism. If it is determine that the control tracing interest principle is not an effective or appropriate mechanism to reduce the inconsistency in South Africa, it should be considered to amend section 7(8) of the ITA (58 of 1962) to include the transfer of property or services to a foreign company held by a foreign trust as an alternative. If the primary mechanism is used, it will eliminate the inconsistency between the CFC regime and the foreign trust provisions in the ITA. The alternative mechanism will not eliminate but reduce the inconsistency by imposing additional tax when a transfer is made by a beneficiary to a foreign company held by a foreign trust.
MCom (Taxation), North-West University, Potchefstroom Campus
Keywords: International tax; anti-avoidance; controlled foreign company; foreign trust